2016
DOI: 10.3389/fpls.2016.00854
|View full text |Cite
|
Sign up to set email alerts
|

QTLs Regulating the Contents of Antioxidants, Phenolics, and Flavonoids in Soybean Seeds Share a Common Genomic Region

Abstract: Soybean seeds are a rich source of phenolic compounds, especially isoflavonoids, which are important nutraceuticals. Our study using 14 wild- and 16 cultivated-soybean accessions shows that seeds from cultivated soybeans generally contain lower total antioxidants compared to their wild counterparts, likely an unintended consequence of domestication or human selection. Using a recombinant inbred population resulting from a wild and a cultivated soybean parent and a bin map approach, we have identified an overla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 39 publications
0
43
0
Order By: Relevance
“…A QTL analysis of the determinants of floral color in cowpea was performed in a biparental mapping population (wild × cultivated crosses; Lo et al, 2018). A single major QTL for floral color, CFcol7, was mapped in a 64-cM region on chromosome Vu07 containing 254 annotated genes, among which a transcription factor, Vigun07g110700, was identified as a homolog of Arabidopsis AT4G09820.1 and Medicago truncatula (Mt) TT8, involved in the regulation of flavonoid biosynthesis (Nesi et al, 2000;Li et al, 2016). In soybean, one QTL for floral pigmentation was identified on linkage group G (Josie et al, 2007).…”
Section: Pigmentation-related Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…A QTL analysis of the determinants of floral color in cowpea was performed in a biparental mapping population (wild × cultivated crosses; Lo et al, 2018). A single major QTL for floral color, CFcol7, was mapped in a 64-cM region on chromosome Vu07 containing 254 annotated genes, among which a transcription factor, Vigun07g110700, was identified as a homolog of Arabidopsis AT4G09820.1 and Medicago truncatula (Mt) TT8, involved in the regulation of flavonoid biosynthesis (Nesi et al, 2000;Li et al, 2016). In soybean, one QTL for floral pigmentation was identified on linkage group G (Josie et al, 2007).…”
Section: Pigmentation-related Traitsmentioning
confidence: 99%
“…ATP-binding cassette transporters and multidrug and toxic compound extrusion transporters play important roles in the secretion and accumulation of secondary metabolites (Yazaki, 2005;Ku et al, 2020). These transporters are associated with microbe interaction and nutrient accumulation of legumes (Sugiyama et al, 2007;Zhang et al, 2010;Fondevilla et al, 2011;Li et al, 2016).…”
Section: Transportersmentioning
confidence: 99%
“…(2) Other studies on seed antioxidant, phenolics, and flavonoid contents have identified GmMATE1, 2, 4 genes [29]. Astringent taste in soy products is caused by group A saponins.…”
Section: Other Traitsmentioning
confidence: 99%
“…(6) A phosphatase 2C-1 (PP2C-1) allele has been reported from wild soybean to be involved in seed weight and seed size. Apart from these genes many QTLs related to (7) linolenic acid production, (8) yield, height and maturity, (9) soybean cyst nematode, (10) seed yield, seed weight, seed filling period, maturity, plant height, and lodging, (11) salt tolerance, (12) sclerotinia stem rot, (13) root traits, (14) oil and local breeding, (15) shoot fresh weight, (16) seed antioxidant, phenolics and flavonoids, and many other traits have been mapped and identified from wild soybeans or populations developed by crossing wild and cultivated soybeans [24,29,[34][35][36][37][38][39][40][41]. Taking the advantage of higher genetic diversity and identified genes and QTLs for important traits from wild soybean will gear up the soybean yield improvement in changing climatic conditions and modern dietary demands.…”
Section: Other Traitsmentioning
confidence: 99%
“…In soy, the content and composition of isoflavonoids are subjected to polygenic regulation and highly variable in response to drought, temperature, fertilization, carbon dioxide content and genetic factors [13]. The level of isoflavonoids is higher in wild-growing populations than in cultivated soybean; this situation is thought to be a consequence of domestication [14].…”
Section: Biosynthesis and Regulationmentioning
confidence: 99%